Mycobacterium tuberculosis Rv2536 protein implicated in specific binding to human cell lines (2005)
The gene encoding the Mycobacterium tuberculosis Rv2536 protein is present in the Mycobacterium tuberculosis complex (as assayed by PCR) and transcribed (as determined by RT?PCR) in M. tuberculosis H37Rv, M. tuberculosis H37Ra, M. bovis BCG, and M. africanum strains. Rabbits immunized with synthetic polymer peptides from this protein produced antibodies specifically recognizing a 25?kDa band in mycobacterial sonicate. U937 and A549 cells were used in binding assays involving 20?amino?acid?long synthetic peptides covering the whole Rv2536 protein sequence. Peptide 11207 (161DVFSAVRADDSPTGEMQVAQY180) presented high specific binding to both types of cells; the binding was saturable and presented nanomolar affinity constants. Cross?linking assays revealed that this peptide specifically binds to 50 kDa U937 cell membrane and 45 kDa A549 cell membrane proteins.